Polygenic scores: Are they a public health hazard?. (December 2019) - Baverstock, Keith
Abstract: I argue here that polygenic scores are a public health hazard because the underlying methodology, genome wide association, from which they are derived, incorrectly assumes that the information encoded in the genomic DNA sequence is causal in terms of the cellular phenotype. This is not so when the cell is viewed from the perspective of a) fundamental physics, b) the protein chemistry that characterises the cellular cytoplasm and c) the fundamental requirement for evolution to yield unlimited species diversity.